Associations of fundus tessellation, myopic diffuse chorioretinal atrophy and choroidal thickness with visual acuity in myopia - Jonas, Jost B.; Panda-Jonas, Songhomitra; Xu, Jie; Wei, Wen Bin; Wang, Ya Xing (Acta ophthalmologica, 2025)
Purpose To explore associations between stages of myopic macular degeneration (MMD) and visual acuity and influencing parameters. Methods Participants of the population-based study Beijing Eye Study (n = 3468 participants) underwent a detailed ocular and systemic examination. Results Assessable images were available for 3040 (87.7%) individuals (age: 64.0 ± 9.7 years). In multivariable analysis, worse best-corrected visual acuity (BCVA) (i.e. higher logMAR values) was associated with higher MMD stage (beta: 0.11; B: 0.06; 95% CI: 0.04, 0.08; p < 0.001) and thinner subfoveal choroidal thickness (beta: −0.06; p = 0.002), with adjustments for age, sex, educational level, cognitive function, degree of any cataract and prevalence of glaucoma, diabetic retinopathy and age-related macular degeneration. If only eyes with MMD grade 1 or no MMD were included, worse BCVA was associated (multivariable analysis) with higher prevalence of MMD stage 1 (beta: 0.11; B: 0.07; 95% CI: 0.05, 0.09; p < 0.001) and thinner medium-sized choroidal vessel layer thickness. Correspondingly, BCVA was worse in eyes with MMD stage 1 than in eyes without MMD (0.13 ± 0.27 logMAR vs. 0.04 ± 0.14; p < 0.001). Including only eyes without vision-influencing disorders (except myopia), BCVA was also worse in eyes with MMD stage 1 than in eyes without MMD (0.06 ± 0.13 logMAR vs. −0.01 ± 0.08 logMAR; p < 0.001). In these eyes without vision-influencing ocular disorders, worse BCVA was associated with thinner total subfoveal choroidal thickness (beta: −0.15; R: 0.000; 95% CI: 0.000, 0.000; p < 0.001) and longer axial length (beta: 0.14; R: 0.01; 95% CI: 0.01, 0.02; p < 0.001), or alternatively with higher MMD staging (beta: 0.24; R: 0.09; 95% CI: 0.01, 0.11; p < 0.001). Conclusions MMD stage 1 (fundus tessellation) is associated with decreased BCVA and may be considered pathological. Independently of longer axial length, thinner choroidal thickness is a factor associated with lower BCVA in myopic eyes, including eyes with MMD stage 1.
Gesehen am 02.09.2025